THE STABILITY OF CHLOROGENIC ACID IN SYRUP OF COFFEE ARABICA (COFFEA ARABICA L.) EXTRACT WITH DECAFFEINATION PROCESS - Budiman, Arif; Lutfhi, Anggi; Muchtaridi, Muchtaridi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This research aims to formulate syrup of coffee arabica extract with decaffeination process and stability test of caffein and chlorogenic acid in syrup of coffee arabica extract. Methods: An extraction was conducted by using ethanol 70% with soxhletation methods, and decaffeination process (using liquid-liquid extraction with ratio of etanol and dicloromethan was 1:1). Syrup formulations of coffee arabica extract was made with various concentrations of Na CMC (thickening agent) and sucralose (flavoring agent). The stability of syrup was evaluated through organoleptic, pH, viscosity, hedonic test, microbiological test and determinated concentration of caffeine and chlorogenic acid. Result: The result showed that the concentration of caffeine before and after decaffeination process were 3.377 + 0091% and 1.028 + 0.079%. While, chlorogenic acid were 4.159 + 0.163% and 3.019 + 0.138%. Microbiological test showed that no contamination in syrup of coffee arabica extract. The concentration of caffeine in syrup of coffee arabica extract was 1.070 + 0.150% and chlorogenic acid was 4.432 + 1.98 %. Conclusion: The concentration of caffeine before and after formulation process were 3.019 + 0.138% and 4.432 + 1.986%. The best formula of coffee arabica extract syrup was the formula that contains 5 mg/ml of coffee arabica extract, 1.5 mg/ml of Na CMC and 0.5 mg/ml of sucralose and no contamination in syrup of coffee arabica extract. Caffeine content would decrease after the decaffeination process.